Embryonic mortality of Indian major carps in some eco-hatchery systems - Rath, S C; Mondal, B; Gupta, S D (Indian Journal of Fisheries, 2011)
Indian major carps viz. Catla catla (Ham.), Labeo rohita (Ham.), and Cirrhinus mrigala (Ham.) are induced bred in eco-hatchery system. Mortality of developing embryo in the incubation system are common which have been investigated at different eco-carp hatcheries in India during 1986-2000. Investigation and experiments were conducted by repeating breeding and incubating the eggs simulating the conditions under which mortality occurred earlier. The investigations have revealed that mortality incidences are due to various factors such as shedding of unprime gametes, teratogenic developments and premature hatchings which are usually followed by fungal infestations. Ovulated oocytes, if not activated, do not imbibe water and die instantly. Some eggs are activated but do not cleave and pass away. Some activated eggs undergo teratogenic development at different stages of embryogenesis such as unequal cleavage, erosion of active blastomeres and improper gastrulation. The teratogenic embryo either died before hatching or hatched out as deformed hatchling but later died due to innate deficiencies. Embryonic mortality instances are recorded more during early and delayed spawning. Partial or mass mortality is also caused by choriolysis and premature hatching. Choriolysis occur due to low oxygen tension (3 ppm) and higher total alkalinity (> 150 ppm) followed by fungal infestation. When embryonic mortality was considerably high (30%-40% of total eggs), usually it led to mass mortality. Some precautionary measures and simple hatchery management practices have resolved the problem.